Case Report: A novel chemotherapy-free regimen combined with photodynamic therapy, target therapy, and immunotherapy in a geriatric male with huge recurrent scalp and facial angiosarcoma: a report of an extremely rare case and literature review - Maswikiti, Ewetse Paul; Feng, Zedong; Yin, Zhenyu; Zhang, Fan; He, Lijuan; Gu, Baohong; Xiang, Lin; Li, Huixia; Wang, Caijuan; Yu, Yang; Xu, Bo; Wang, Jize; et al. (Frontiers in Immunology, 2025)
Angiosarcomas are sporadic vascular neoplasms among the most aggressive subtypes of soft tissue sarcomas. In addition, vast and multiple recurrent superficial scalp and facial angiosarcomas are very complex and extremely difficult to manage. Their occurrence brings about significant social and emotional distress to affected individuals. To date, no specific therapeutic strategy has been the most effective and reliable. Herein, we report a highly unique case of a geriatric male patient with recurrent scalp and facial angiosarcoma successfully treated by a chemotherapy-free regimen consisting of photodynamic therapy (PDT), immunotherapy, and target therapy. Notably, PDT provided promising remarkable auspicious outcomes and proved to be a better therapeutic option for refractory malignant angiosarcomas.